RELASI SOSIAL ASOSIATIF DALAM KELOMPOK TANI DEWI RATIH KECAMATAN MEMPAWAH HILIR KELURAHAN TERUSAN - Enifika, Dwi Rezki; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine associative social relations in the farmer Group of Dewi Ratih Sub-district, Mempawah Hilir subdistrict. The research methods used are descriptive with a form of qualitative research. The source of this research data is farmer group Dewi Ratih. The data collection techniques in this research are through observation, interviews, and documentation, while the data collection tools used are observation guides, interview guides, and notebooks, and archives. The analysis in this study presented in a qualitative descriptive using the informant of four people, consisting of the Chairman of the farmer group Dewi Ratih, members of the farmer group Dewi Ratih, field agriculture extension, and head of the agriculture extension Hall. The results of this study show that there are associative social relations in the form of cooperation in the farmer group Dewi Ratih especially in spontaneous, direct, and traditional cooperation. Although not all members but some farmer groups Dewi Ratih have cooperation in harvesting rice, rice planting, eradicating pests, there is a tradition of rejecting seeds and participating in counseling.Keywords: Farmer group, Associative, Social Relations.